2015
DOI: 10.1016/j.jes.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable promotion effect of trace sulfation on OMS-2 nanorod catalysts for the catalytic combustion of ethanol

Abstract: OMS-2 nanorod catalysts were synthesized by a hydrothermal redox reaction method using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…17,20,30 Nevertheless, the surface acid properties, including the type and strength of acid sites of the catalysts, generally change little in these investigations, which makes the promotion effects become very limited. Recently, some researchers have found that the introduction of SO 4 2− into the catalyst by sulfuric acid treatment significantly promotes the surface acidity, which thus improves the catalytic performance including ethanol oxidation, 31 selective catalytic reduction of NO x by ammonia, 32−34 n-butane isomerization, etc. 35,36 However, the possibility of promoting the catalytic ozonation of toluene by introducing SO 4 2− into catalysts has not been investigated until now.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,20,30 Nevertheless, the surface acid properties, including the type and strength of acid sites of the catalysts, generally change little in these investigations, which makes the promotion effects become very limited. Recently, some researchers have found that the introduction of SO 4 2− into the catalyst by sulfuric acid treatment significantly promotes the surface acidity, which thus improves the catalytic performance including ethanol oxidation, 31 selective catalytic reduction of NO x by ammonia, 32−34 n-butane isomerization, etc. 35,36 However, the possibility of promoting the catalytic ozonation of toluene by introducing SO 4 2− into catalysts has not been investigated until now.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been recently reported that Lewis and Brönsted acid sites play an important role in the catalytic ozonation of toluene. ,, Some strategies of enhancing the acid sites of the catalyst, including doping metal oxides, hydrogenation, and high-temperature calcination, have been testified to be effective for promoting the catalytic ozonation of toluene. ,, Nevertheless, the surface acid properties, including the type and strength of acid sites of the catalysts, generally change little in these investigations, which makes the promotion effects become very limited. Recently, some researchers have found that the introduction of SO 4 2– into the catalyst by sulfuric acid treatment significantly promotes the surface acidity, which thus improves the catalytic performance including ethanol oxidation, selective catalytic reduction of NO x by ammonia, n -butane isomerization, etc. , However, the possibility of promoting the catalytic ozonation of toluene by introducing SO 4 2– into catalysts has not been investigated until now.…”
Section: Introductionmentioning
confidence: 99%
“…Manganese oxides have been considered as unique materials for redox catalysis because of their polyvalent nature, novel chemical and physical properties, low cost and environmentally benign features (Tang et al, 2006a(Tang et al, , 2006bLi et al, 2009). MnO 2 is an excellent catalyst for the oxidation of volatile organic compounds, and much research has been focused on its catalytic properties (Liang et al, 2008;Saputra et al, 2013;Zhang et al, 2015). Further, manganese ions were found to induce Fenton-like reactions for the oxidation of phenol and decolorization of methylene blue (Zhang et al, 2006;Saputra et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…cryptomelane OMS-2[159,160]. Cryptomelanes KMn8O16 prepared by a sol-gel technique (KMnO4 in fumaric acid) or by a reflux method (KMnO4 added to a boiling solution of Mn acetate in acetic acid) show the best performance in ethanol oxidation (T50 at 120°C)[159].…”
mentioning
confidence: 99%
“…Sulfate-doped OMS-2 are more active than undoped catalysts. A suitable amount of SO4 2− species into the OMS-2 catalyst could decrease the Mn-O bond strength and also enhance the lattice oxygen concentration and number of acid sites, which then effectively promoted the catalytic activity of OMS-2[160]. Co-Mn-Al mixed oxides of spinel structure were prepared by Kovanda et al by calcination of layered double hydroxides (LDH) precursors deposited on anodized aluminum[161].They are more active in ethanol oxidation (T50 = 123 °C) than mixed oxides formed from coprecipitated salts (T50 ranging from 150 to 190°C).…”
mentioning
confidence: 99%